Integrating artificial intelligence into healthcare systems: opportunities and challenges - Bongs Lainjo (Academia Medicine)
This article examines the integration of artificial intelligence (AI) in healthcare, highlighting both the opportunities and challenges it presents. AI offers significant advancements in healthcare, such as improving diagnostic accuracy, streamlining workflow processes, and enhancing patient care. The article synthesizes evidence from empirical studies and scholarly literature, with a focus on credible and reputable sources. Research indicates that AI has transformed healthcare innovation, particularly in clinical decision support and personalized treatment. However, the adoption of AI is not without challenges. Ethical and legal concerns, including patient privacy, remain prominent obstacles. Technical limitations, such as inconsistent risk management across healthcare settings and the need for reliable IT infrastructure, further complicate AI implementation. Moreover, the development of high-quality and diverse datasets is essential to improve data sharing and enhance decision-making accuracy in healthcare. While tools like telemedicine and remote patient monitoring improve access to care, they also increase the risk of unauthorized data breaches. To address these concerns, healthcare organizations must promote a culture of accountability, ensuring that healthcare providers remain vigilant about patient data security. Overall, the article underscores the potential of AI to revolutionize healthcare while emphasizing the need to address the ethical, technical, and security challenges it brings.